Investigation of the effect of different silane coupling agents on mechanical performance of basalt fiber composite laminates with biobased epoxy matrices. Issue 3 (7th February 2013) - España, J.M.; Samper, M.D.; Fages, E.; Sánchez‐Nácher, L.; Balart, R.
Abstract In recent years, it has been detected an increased interest in the development of materials from renewable resources. This trend has been intensified in the industrial sector where significant efforts have been made in this field in order to adapt these natural fibers to conventional industrial processes and applications. As a result, research has been done into developing new thermoplastic matrices which are compatible with this type of reinforcing fibers. This study evaluates the influence of different coupling agents based on silanes, on the mechanical properties of composite laminates made from a biobased epoxy resin matrix and basalt fabric by using vacuum assisted resin transfer moulding. The curing behavior of the biobased epoxy resin was evaluated by differential scanning calorimetry (DSC), gel point determination, and ionic conductivity. The evaluation of mechanical properties was done by tensile, flexural, impact, and hardness tests. Compatibility between basalt fibers and epoxy resin generally has managed to increase through the addition of silanes, after the addition of these, their mechanical properties are substantially improved compared to the sample without silane treatment, obtaining this way an easily processable material, with good properties and capable of competing with materials with petroleum‐based epoxy resins. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers